The Official (ISC)2 SSCP CBK Reference / Mike Wills - Wills, Mike (WILEY-SYBEX, 2019)
The only official body of knowledge for SSCP'(ISC)2's popular credential for hands-on security professionals'fully revised and updated. Systems Security Certified Practitioner (SSCP) is an elite, hands-on cybersecurity certification that validates the technical skills to implement, monitor, and administer IT infrastructure using information security policies and procedures. SSCP certification'fully compliant with U.S. Department of Defense Directive 8140 and 8570 requirements'is valued throughout the IT security industry. The Official (ISC)2 SSCP CBK Reference is the only official Common Body of Knowledge (CBK) available for SSCP-level practitioners, exclusively from (ISC)2, the global leader in cybersecurity certification and training. This authoritative volume contains essential knowledge practitioners require on a regular basis. Accurate, up-to-date chapters provide in-depth coverage of the seven SSCP domains: Access Controls; Security Operations and Administration; Risk Identification, Monitoring and Analysis; Incident Response and Recovery; Cryptography; Network and Communications Security; and Systems and Application Security. Designed to serve as a reference for information security professionals throughout their careers, this indispensable (ISC)2guide: -Provides comprehensive coverage of the latest domains and objectives of the SSCP -Helps better secure critical assets in their organizations -Serves as a complement to the SSCP Study Guide for certification candidates The Official (ISC)2 SSCP CBK Reference is an essential resource for SSCP-level professionals, SSCP candidates and other practitioners involved in cybersecurity.
Keywords: Computers; Ordinateurs; computers; COMPUTERS; Security; Networking